Fingerprint Image Denoising Method Based on Improved Threshold Function - ZHANG Zhao-ru; DENG Cai-xia; YUE Xin-hua (Journal of Harbin University of Science and Technology, 2022)
In order to make fingerprint identification technology more accurate and efficient, an improved threshold function is proposed to denoise fingerprint images.First, according to the characteristics of fingerprint images, an improved threshold function is constructed.Compared with traditional soft and hard threshold functions and some existing improved threshold functions, this threshold function has good adjustability, and is adjustable everywhere. It is better to approximate the soft threshold function, and the image at the threshold point is smoother.When denoising the image, it can retain more real information on it and effectively filter out the noise-Simulation experiments show that the improved threshold function has high peak signal-to-noise ratio and structure similarity, small root mean square error and distortion degree, and better correlation coefficient, and can be closer to the original image.Therefore, the improved threshold function has good application value.